FRIENDS OF GOOD MUSIC: A CASE STUDY ON THE MEMORIES OF THE MUSIC SECTOR IN THE CITY OF BAURU - Serra, Camila Roberta Muniz; Carvalho, Juliano Mauricio de [UNESP] (Programa Pos-graduacao Musica-ppgm, 2023)
This article presents the Club Amigos da Boa Musica (ABM) held in the Bauru town since the 1940s. The research problem of this study arises from the investigation around the changes in the music sector in the context of the creative industry starting from of the ABM Club. To achieve the objective of presenting the trajectory of the Club Amigos da Boa Musica in the Bauru town in the context of the creative industry, bibliographical research was carried out with reference to concepts related to musical art, music, the creative industry and the music sector. Then, a case study was carried out identifying the motivations for the initiative in the Bauru town, as well as its resumption; the stages for the organization and promotion of this initiative in the city; the impact of this event on the city's music industry and club participants; the investment required for the meetings to take place; and the profile of the team of organizers of the meetings in the city. After reporting on ABM from its creation to the present day, changes that the club has undergone over the years were identified, observing the evolution and protagonism of recording technologies and their importance in the music sector in the Bauru town. Club ABM's eighty-year path illustrates aspects of the creative industry, emphasizing the importance of creativity in the job market, favoring the economy, technology and culture, the context in which the club is inserted in the construction of its history.
Keywords: Cultural industry; Creative industry; Friends of Good Music; Music sector in Bauru town